Kandungan Gizi Ikan Lundu (Macrones gulio) Sebagai Bahan Baku Diversifikasi Produk - Mutiara Mutiara; Susi Lestari; Wulandari Wulandari; Herpandi Herpandi; Dwi Inda Sari (Jurnal FishtecH, 2022)
Catfish (Macrones gulio) is a freshwater fish that is widely distributed in the waters of South Sumatra. Information on the nutritional content of in Macrones gulio order to provide information on the nutritional value of lundu fish and can increase the prospects for product development can be displayed. The purpose of this study was to determine the nutritional composition of lundu fish. This research method used a completely randomized design (CRD) with 4 treatment factors, namely whole, fillet with skin, head, and bones and fins each performed 3 times in a row. Work procedures complete with sample preparation and collection, sample preparation and proximate analysis. Parameters observed were water content, fat content, protein content, ash content and carbohydrates. The different preparations on the body parts of lundu fish provide different nutritional content in each preparation treatment. Catfish (Macrones gulio) contains 14.52%-16.37% protein, 1.765%-11.76% ash, 2.06%-4.7% fat, and 0.72%%-11.56% carbohydrate content.